Biodiversity, ecosystem functioning, and human wellbeing an ecological and economic perspective - Naeem, Shahid (Oxford Oxford University Press, 2009)
Biodiversity change is one of the most controversial and high profile areas of ecological research. This text provides an in-depth evaluation of the science and its implications and applications to some of the most pressing environmental issues facing humans today.
Description based on print version record.
Includes bibliographical references (p. 299-356) and index.
Keywords: Biodiversity; Biodiversity -- Monitoring -- Economic aspects; Ecosystem health; Ecological assessment (Biology); Ecological assessment (Biology) -- Economic aspects; Human beings -- Effect of environment on; Electronic books; Electronic books